Strategic Development of Capital-intensive Sectors in Coastal East Java: Infrastructure-energy Integration and Input-output Policy Simulation 2025 - Samas Adimisa Mishbah Habibie; Ribut Santoso; Yusma Abinaya Tahsina Akmal; Daffa Akbar Azhar (East Java Economic Journal, 2026)
East Java, Indonesia’s second-largest economic contributor, holds strategic potential for capital-intensive industrial transformation, particularly in its coastal regions, which are endowed with surplus electricity, natural gas, and port access. This study applies a regional input–output framework to simulate the economic impacts of infrastructure–energy integration on key sectors. Four policy scenarios are examined: business as usual, infrastructure acceleration, energy optimization, and integrated infrastructure–energy intervention, focusing on gross regional domestic product (GRDP), sectoral output, employment multipliers, and intersectoral linkages. The results indicate that the integrated scenario yields the most transformative outcomes, with GRDP growth reaching 6.7%, the highest employment multiplier of 1.45, and substantial output increases in construction (+58.65%) and manufacturing (+49.71%). These findings highlight that synchronized infrastructure and energy policies generate stronger systemic spillovers than isolated interventions, reinforcing forward and backward linkages while enhancing regional competitiveness. The study contributes to regional development discourse by providing evidence-based insights on how infrastructure–energy synergies can accelerate structural transformation in coastal East Java. Furthermore, it aligns with Indonesia’s 2025 national agenda under the Red-and-White Cabinet, emphasizing downstream industrialization, energy sovereignty, and localized resilience.